Kalibrasi Dosimeter Saku Gamma Meggunakan Sumber Radioaktif Cesium-137 di Balai Pengamanan Fasilitas Kesehatan (BPFK) Makassar - Sitti,; Nurul Fuadi,; Miftahul Janna,; Ika, (SAINFIS: Jurnal Sains Fisika, 2023)
Calibration is an activity to determine the conventional truth of the designation value of measuring instruments and measuring materials by comparing them to traceable measuring standards to national and international standards for international units of measurement and certified reference materials. AUR calibration is the act of comparing the readings of the instrument against the standard AUR readings or the act of irradiating the device in a radiation field of known characteristics through a standard source or standard AUR at reference conditions. Personal dosimeter is a tool used to measure the cumulative radiation dose. The tools and materials used in this practicum are personal dosimeter (ARROW-TECH), thermohygrobarometer, irradiator, cesium-137 radiation source, laser, steel ruler, compressor, CCTV monitor, zero dosimeter, plaster and panthom. From the measurement results that have been carried out, the measurement data obtained are 1,510 mSv, 1,510 mSv, 1,500 mSv, 1,500 mSv and 1,500 mSv. So that the value of the personal dosimeter calibration factor is 1.07. Where the calibration factor is generated from the comparison between the standard dose and the average measurement results.